العلاقة بين مستوى الزنك المصلي و الحاصة البقعية - خدام, جمال; اسماعيل, مروه (Latakia University Journal -Medical Sciences Series, 2019)
Background Alopecia areata (AA) is a non-scarring, autoimmune, inflammatory hair loss disease. Zinc is a trace element involved in important functional activities of hair follicles. Purpose To evaluate serum zinc level in AA patients in comparison to age- and sex-matched healthy controls. Methods The present study included 96 subjects: 48 patients with AA and 48 age- and sex-matched healthy controls. Serum zinc levels were assessed in all subjects. Comparison of mean serum zinc levels was done between all patients and controls. Correlations between serum zinc level and extent of AA and its duration were also done in all patients. Results serum zinc levels were significantly lower in patients with AA than control individuals (91.5 ± 21.8 vs. 107.7 ± 16.5, P-v=0.001) . Significant inverse correlations existed between serum zinc level, severity of AA, and disease duration in all patients . Conclusion Lower serum zinc level existed in patients with AA and correlated inversely with disease duration, severity of AA. And this suggests its possible role in the pathogenesis of AA. Accordingly, zinc supplements may provide a therapeutic benefit. مقدمة :الحاصة البقعية مرض مناعي ذاتي، التهابي يسب تساقط غير مندب للشعر. الزنك هو عنصر زهيد يقوم بوظائف حيوية هامة في الجريب الشعري . هدف الدراسة: تقييم مستوى الزنك المصلي عند مرضى الحاصة البقعية ومقارنته مع مستواه لدى مجموعة من الأصحاء المقاربين لمجموعة المرضى من حيث العمر و الجنس . المواد و الطرائق: ضمت هذه الدراسة 96 شخصا : 48 مريض حاصة بقعية و 48 شاهد غير مصاب بالحاصة البقعية .تم قياس مستويات الزنك المصلية عند كل أفراد الدراسة .تمت مقارنة متوسطات مستويات الزنك عند المرضى ومجموعة الشاهد.وتمت دراسة ارتباط مستوى الزنك في المصل مع كل من شدة و مدة الحاصة البقعية عند المرضى . النتائج: مستويات الزنك المصلي كانت أقل بشكل هام عند مرضى الحاصة البقعية مقارنة مع مجموعة الشاهد (91.5 ± 21.8 مقابل 107.7 ± 16.5 و P-v=0.001 ). وجد ارتباط سلبي هام بين مستوى الزنك المصلي مع شدة الحاصة البقعية و مدة الإصابة عند المرضى . الخلاصة: مستويات أقل للزنك وجدت في مصل مرضى الحاصة البقعية وكما كان هناك ارتباط سلبي بينها و بين شدة المرض و مدته و هذا يقترح احتمالية وجود دور لنقص الزنك في إمراضية الحاصة البقعية .و بذلك قد يكون لإعطاء مكملات الزنك فائدة علاجية .